Kinetic Characterization of Yeast Pyruvate Carboxylase Isozyme Pyc1 and the Pyc1 Mutant, C249A - Joy P. Branson (2018)
The yeast Pyc1 isoform of pyruvate carboxylase has been further characterized and shown to differ from the Pyc2 isoform in its Ka for K+ activation. Pyc1 differs from chicken liver pyruvate carboxylase in the lack of effect of acetyl-CoA on ADP phosphorylation by carbamoyl phosphate, which may be a result of differences in the loci of action of the effector between the two enzymes. Solvent D2O isotope effects have been measured with Pyc1 on the full pyruvate carboxylation reaction, the ATPase reaction in the absence of pyruvate, and the carbamoyl phosphate-ADP phosphorylation reaction for the first time for pyruvate carboxylase. Proton inventories indicate that the measured isotope effects are due to a single proton transfer step in the reaction. The inverse isotope effects observed in all reactions suggest that the proton transfer step converts the enzyme from an inactive to an active form. Kinetic measurements on the C249A mutant enzyme suggest that C249 is involved in the binding and action of enzyme activators K+ and acetyl-CoA. C249 is not involved in ATP binding as was observed for the corresponding residue in the biotin carboxylase subunit of Escherichia coli acetyl-CoA carboxylase, nor is it directly responsible for the measured inverse D(kcat/Km) isotope effects. The size of the inverse isotope effects indicates that they may result from formation of a low-barrier hydrogen bond. Modification of the wild type and C249A mutant with o-phthalaldehyde suggests that C249 is involved in isoindole formation but that the modification of this residue is not directly responsible for the accompanying major loss of enzyme activity.